Currency substitution in a de-dollarizing economy: the case of Russia - Barry Harrison; Yulia Vymyatnina (Bank of Finland, Institute for Economies in Transition (BOFIT), 2007)
Currency substitution, the use of foreign money to finance transactions between domestic residents, is a common feature of emerging market economies.Currency substitution reduces the stability of money demand functions in ways that can seriously undermine central bank credibility and its efforts to implement monetary policy.Most transition economies, including Russia, experienced widespread currency substitution in the early phase of transition.Following Russia's financial meltdown in 1998, its monetary authorities introduced a raft of changes that substantially improved the stability and performance of the macroeconomy and reduced currency substitution.This paper investigates currency substitution in the Russian economy in the post-crisis period of 1999-2005.Several measures of currency substitution and different modelling frameworks consistently suggest an on-going decline in currency substitution, a shift that has important implications for Russian monetary policy.
URN:NBN:fi:bof-201408071961
Keywords: E58; F31; F41; 330; currency substitution; transition economies; de-dollarization